Kara umowna za brak lub nieterminową zapłatę wynagrodzenia podwykonawcom — uwagi na tle uchwały Sądu Najwyższego z dnia 30 czerwca 2020 roku, III CZP 67/19 - Herl, Cyprian (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The subject of this work is the issue of the admissibility of stipulating liquidated damages for failure to pay or delayed payment of remuneration to subcontractors in the light of article 483 par. 1 of the Civil Code, which allows stipulating contractual penalties only in non-pecuniary obligations. The basis for the considerations is the content of the resolution of the Supreme Court of June 30th, 2020 (III CZP 67/19), which took a firm position in the ongoing legal discourse. This publication is a comparison on the basis of the previous jurisprudence and the doctrine of the relationship between liquidated damages defined in article 483 par. 1 of the Civil Code, and liqui-dated damages provided for in the Act of 29th January 2004 — Public Procurement Law.
Keywords: liquidated damages in public procurement contracts; subcontractors in public procurement; performance of the obligation and the consequences of non-performance; non-pecuniary obligations